2013
DOI: 10.1016/j.chom.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Host-Intestinal Microbiota Mutualism: “Learning on the Fly”

Abstract: Given the complexity of the mammalian microbiota, there is a need for simple models to decipher the effector and regulatory mechanisms underlying host/microbiota mutualism. Approaches using Drosophila and its simple microbiota carry the potential to unravel the evolutionarily conserved mechanisms engaged in this association. Here, we review recent work carried out in this model, providing insights and exciting perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
172
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 36 publications
0
172
0
Order By: Relevance
“…There has recently been a resurgence in research on animal-microbiome interactions in which fruit flies are emerging as an important model system (Erkosar et al, 2013). Our work links such research, which has focused on mechanisms of such interactions, with animal behaviour and ecology.…”
Section: Prospectsmentioning
confidence: 98%
See 1 more Smart Citation
“…There has recently been a resurgence in research on animal-microbiome interactions in which fruit flies are emerging as an important model system (Erkosar et al, 2013). Our work links such research, which has focused on mechanisms of such interactions, with animal behaviour and ecology.…”
Section: Prospectsmentioning
confidence: 98%
“…Volatiles from both L. brevis, which we cultured from our fly population, and L. plantarum, which has been isolated from the Drosophila gut in other studies, were attractive. These two bacterial species are common constituents of the fruit-fly microbiome in both laboratory and field populations (Chandler et al, 2011;Erkosar et al, 2013). It would be interesting to see whether other major species of the fruit fly microbiome also produce volatiles attractive to fruit flies.…”
Section: P=01mentioning
confidence: 99%
“…Although some microbes are parasites that can cause disease, many others lie on the spectrum between commensalism and mutualism and may significantly influence their hosts' nutrition (Dethlefsen et al, 2007), development (Bates et al, 2006) and disease resistance (Macpherson and Harris, 2004;Koch and Schmid-Hempel, 2011). The use of model organisms such as the fruit fly Drosophila melanogaster, the nematode Caenorhabditis elegans, the house mouse Mus musculus and the zebrafish Danio rerio has facilitated understanding of the mechanisms by which certain biological functions of the hosts are modulated by their microbiota (Rawls et al, 2004;Turnbaugh et al, 2006;Cabreiro and Gems 2013;Erkosar et al, 2013). As interest in environmental genomics emerges, the roles of microbiota in the ecology and evolution of an increasing number of non-model organisms are being investigated, revealing a high diversity in the types of effects observed (Fraune and Bosch, 2010;Engel et al, 2012;Koch and Schmid-Hempel, 2011;Brucker and Bordenstein, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria-free zebrafish exhibit visible degeneration of intestinal tissues by day 8 post fertilization and have 100% mortality by day 20 unless bacteria are re-introduced (Rawls et al, 2004). Bacteria-free Drosophila larvae have slowed or arrested development depending on dietary conditions (Erkosar et al, 2013), and germ-free adult flies have been reported to have reduced lifespan compared with conventional flies (Brummel et al, 2004). The development and lifespan of the nematode C. elegans, on the other hand, is twice as long when cultured in axenic conditions (Houthoofd et al, 2002), whereas addition of live Escherichia coli restores its normal life history (Lenaerts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the intestinal tract of the fruit fly is anatomically and physiologically similar to the mammalian gut, [18] yet the microbial composition is rather simple: Throughout the larval and adult life, the fly gut hosts five to twenty aero-tolerant commensal species, all of which are readily cultured in the laboratory. [19,20] Two families of bacteria: Acetobacteraceae and Lactobacillaceae, dominate the community. [21][22][23][24][25][26] However, the fly gut microbiota is transient in nature and requires constant replenishment; thus, the community structure and bacterial load fluctuate highly as the flies develop and age.…”
mentioning
confidence: 99%